20 ans après: a second mutation in MAOA identified by targeted high-throughput sequencing in a family with altered behavior and cognition - Piton, Amélie (Nature Publishing Group, 2014)
Intellectual disability (ID) is characterized by an extraordinary genetic heterogeneity, with >250 genes that have been implicated in monogenic forms of ID. Because this complexity precluded systematic testing for mutations and because clinical features are often non-specific, for some of these genes only few cases or families have been unambiguously documented. It is the case of the X-linked gene encoding monoamine oxidase A (MAOA), for which only one nonsense mutation has been identified in Brunner syndrome, characterized in a single family by mild non-dysmorphic ID and impulsive, violent and aggressive behaviors. We have performed targeted high-throughput sequencing of 220 genes, including MAOA, in patients with undiagnosed ID. We identified a c.797_798delinsTT (p.C266F) missense mutation in MAOA in a boy with autism spectrum disorder, attention deficit and autoaggressive behavior. Two maternal uncles carry the mutation and have severe ID, with a history of maltreatment in early childhood. This novel missense mutation decreases MAOA enzymatic activity, leading to abnormal levels of urinary monoamines. The identification of this new point mutation confirms, for the first time since 1993, the monogenic implication of the MAOA gene in ID of various degrees, autism and behavioral disturbances. The variable expressivity of the mutation observed in male patients of this family may involve gene–environment interactions, and the identification of a perturbation in monoamine metabolism should be taken into account when prescribing psychoactive drugs in such patients.